2022
DOI: 10.1097/jxx.0000000000000788
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of motivating factors and barriers to precepting

Abstract: Background: Advanced practice registered nurses (APRNs) and physician assistants (PAs) are integral to health care delivery in the United States. However, the cultivation of APRNs and PAs relies heavily on the model of precepting. Advanced practice registered nurses and PAs frequently precept students or new hires, yet limited data are available to describe the motivations, incentives, and barriers associated with precepting.Purpose: The purpose of this mixed-method, cross-sectional study was to better underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In a recent study published in 2022, Boyce et al once again identified communication and support from PA programs as a key area of opportunity to improve the relationship with preceptors. 3,37,40 Physician assistant programs could increase the support of preceptors by providing training on structured teaching techniques. Training resources could help ease student instruction burden that preceptors may experience.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study published in 2022, Boyce et al once again identified communication and support from PA programs as a key area of opportunity to improve the relationship with preceptors. 3,37,40 Physician assistant programs could increase the support of preceptors by providing training on structured teaching techniques. Training resources could help ease student instruction burden that preceptors may experience.…”
Section: Discussionmentioning
confidence: 99%
“…Across all health professions, clinical preceptors are an essential part of the clinical training of learners. [1][2][3] Preceptorship allows for individualized learning between an experienced clinician and a novice learner. 4 Frequently, those clinicians who precept are asked to do so based on availability rather than demonstrating competent teaching skills.…”
Section: Role Of Clinical Preceptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those data indicate that compensation and facultypreceptor communication are top preceptor concerns. Preceptors also indicated the need for protected teaching time, preceptor training, and meaningful preceptor recognition (Boyce et al, 2022;Burt, Sparbel, and Corbridge, 2021).…”
Section: -Behavioral Health Representativementioning
confidence: 99%